THU0221 EVIDENCE FOR A PATHOGENIC ROLE OF EXTRA-FOLLICULAR, IL-10 PRODUCING CCR6+B-HELPER T-CELLS IN SYSTEMIC LUPUS ERYTHEMATOSUS. (2nd June 2020) - Gerosa, M.; Facciotti, F.; Larghi, P.; Bosotti, R.; Vasco, C.; Gagliani, N.; Cordiglieri, C.; Rottoli, E.; Penatti, A. E.; Argolini, L. M.; Karnani, B.; Kobayashi, Y.; et al.
Abstract : Background: IL-10 plays a key role in systemic lupus erythematosus (SLE) pathogenesis, promoting B-cell response. IL10 is mainly secreted by regulatory T-cells, but follicular helper T-cells (TFH ), also produce it. We previously identified a subset of CCR6 + IL-7R + T-cells in human tonsils providing IL-10-dependent B-cell help. These CCR6 + T-cells were able to produce IL-10, inducing IgG production. Objectives: to investigate a possible role of CD4 + CCR6 + IL7R + T-cells in SLE pathogenesis. Methods: 37 patients fulfilling the ACR criteria for SLE have been included. Disease activity was assessed by 2k-SLEDAI. PBMC were analyzed by flow cytometry, using specific lineage markers. CCR6 + IL7R + T-cells purified from total PBMC of SLE patients or healthy donors (HD) were co-cultured with autologous CD20 + B-cells. IL-10, Il-17, total IgG and anti-dsDNA antibodies titers in patients serum and culture supernatants were assessed by ELISA. Embedded sections of lymph nodes from 8 SLE patients were analyzed by immunofluorescence (IF). Results: IL10 levels were significantly higher in SLE patients (Fig 1A ). CD4 + CCR6 + IL7R + T-cells were significantly increased in SLE, in particular in those with higher disease activity and higher IL10 levels. CD4 + CCR6 + IL7R + T-cells levels associated with anti-dsDNA positivity. CCR6 + IL7R + T-cells of SLE patients induced production of IgG and anti-dsDNA IgG (in anti-dsDNA + patients) from autologous B-cells, providing spontaneous help for autoantibody production ex vivo (Fig 1B -C). The IF study of lymph nodes of SLE patients showed that IL-10-producing CCR6 + T-cells were highly abundant and co-localized with B-cells at follicle margins. Conclusion: our study revealed a novel population of extra-follicular B-helper T-cells, which produce IL-10 and could play a prominent pathogenic role in SLE. Further studies will clarify if this potentially pathogenic cell population might represent a possible future therapeutic target. References: [1]Facciotti F. J Allergy Clin Immunol. 2016; Geginat J. Semin Immunol. 2019; Tsokos GC. Nat Rev Rheumatol. 2019 Disclosure of Interests: Maria Gerosa: None declared, Federica Facciotti: None declared, Paola Larghi: None declared, Roberto Bosotti: None declared, Chiara Vasco: None declared, Nicola Gagliani: None declared, Chiara Cordiglieri: None declared, Elsa Rottoli: None declared, Alessandra Emiliana Penatti: None declared, Lorenza Maria Argolini: None declared, Bhavna Karnani: None declared, Yasushi Kobayashi: None declared, Mauro Bombaci: None declared, Jan Piet Van Hamburg: None declared, Roberta Gualtierotti: None declared, Stefano Gatti: None declared, Sara Torretta: None declared, Lorenzo Pignataro: None declared, Sander W. Tas: None declared, Roberto Caporali Consultant of: AbbVie; Gilead Sciences, Inc.; Lilly; Merck Sharp & Dohme; Celgene; Bristol-Myers Squibb; Pfizer; UCB, Speakers bureau: Abbvie; Bristol-Myers Squibb; Celgene; Lilly; Gilead Sciences, Inc; MSD; Pfizer; Roche; UCB, Sergio Abrignani: None declared, Massimiliano Pagani: None declared, Fabio Grassi: None declared, Pier Luigi Meroni: None declared, Richard Flavell: None declared, Jens Geginat: None declared